Exploration of the Dempster-Shafer Theory for Diagnosing Hardware Damage: Comparative Study with the Certainty Factor Method - Koidah, Koidah; Basir, Azhar; Jamil, Abdul (Journal of INISTA, 2024)
Comparative research is a research method that compares two or more research objects to expand understanding of them. In this context, we compare the Certainty Factor method and the Dempster-Shafer method in diagnosing computer hardware damage. The Certainty Factor method measures an expert's confidence in the solution that will be provided. On the other hand, the Dempster-Shafer method is a useful theory in situations where uncertainty dominates. This research focuses on comparing the effectiveness of the two methods in detecting computer hardware damage. An experimental approach is used to look for causal relationships between variables controlled by the researcher. The research results show that the Certainty Factor method has an average success rate of 14.51%, while the Dempster-Shafer method reaches 84.27% in terms of error difference. From these results, it can be concluded that the Certainty Factor method is more effective in diagnosing computer hardware damage. Keywords: INISTA, journal, MS.Word template